An Investigation on COVID-19 in Nigeria and Relationship with Age Groups - TM, Enaohwo; W, Ikpama; OG, Okoro; EG, Moke (International Journal of Human and Health Sciences (IJHHS), 2021)
Objective: Coronavirus disease 2019 (COVID-19) was first reported in Wuhan China in December 2019 and has immediately spread to essentially almost every area of the world. The infection is caused by a serious kind of acute respiratory condition known as coronavirus 2 (SARSCoV-2). Aim: The investigation was carried out to determine the knowledge, awareness, and relationship between Coronavirus and different age groups among Nigerians. Materials and Methods: The study recruited nine hundred and ninetyeight (998) participants who were of Nigerian origin and, aged 20 years or more who understood the substance of the banner who looked at its evaluation. A two-page enlistment flag was posted/reposted to groups in Whatsapp, Twitter and, Facebook. This banner contained a short presentation on the establishment, objective, reasoning, purposeful nature of help, attestations of mystery, and security similarly as the association of the practical reaction code of the online survey. Result and Discussion: The outcomes indicated that the majority of the respondents had sound information on COVID-19, 911(91.3%), in this manner knowing it to be a viral contamination. It was additionally observed that a large portion of the respondents, 850 (85.2%) concurred coming up next are manners by which one could get tainted with COVID-19; these among others include; shaking of hands with infected people, contacting objects contacted by infected people and sneezing or coughing by infected people. The outcome further portrays a huge relationship that existed between the members’ age and questions raised on COVID-19 (p<0.001). Conclusion: It is along these lines that it is suggested that all partners ought to heighten their exertion in sharpening the overall population just as network base refinement program be done in other for the residents to comprehend and follow every single prudent step to curb COVID-19 in Nigeria. International Journal of Human and Health Sciences Vol. 05 No. 03 July’21 Page: 292-296